2020
DOI: 10.1029/2020je006556
|View full text |Cite
|
Sign up to set email alerts
|

Gravity Wave Activity in the Atmosphere of Mars During the 2018 Global Dust Storm: Simulations With a High‐Resolution Model

Abstract: Gravity waves (GWs) exist in atmospheres of all planets with convectively stable stratification. They transport energy and momentum from denser tropospheres to thinner upper levels (Yiğit & Medvedev, 2019). Effects produced by GWs are particularly strong in the middle and upper atmospheres of Earth and Mars (see recent reviews of Medvedev & Yiğit, 2019; Yiğit & Medvedev, 2015, correspondingly), thus making them a major dynamical mechanism that couples the lower and upper atmospheres on both planets. Being rela… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 56 publications
(91 reference statements)
5
47
1
Order By: Relevance
“…For instance, the diurnal variability of gravity wave drag is suggested to modify the DW1 propagation in the Earth's atmosphere (Meyer, 1999;Ortland & Alexander, 2006). Recent observation and simulation studies suggested that the diurnal variability of gravity wave activity in the Martian lower atmosphere is significantly reduced during dust storms (Heavens et al, 2020;Kuroda et al, 2020), which could remove its constraint on the DW1. Such effect of small-scale gravity wave flux in modifying the tidal structure on Mars needs more studies in the future.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the diurnal variability of gravity wave drag is suggested to modify the DW1 propagation in the Earth's atmosphere (Meyer, 1999;Ortland & Alexander, 2006). Recent observation and simulation studies suggested that the diurnal variability of gravity wave activity in the Martian lower atmosphere is significantly reduced during dust storms (Heavens et al, 2020;Kuroda et al, 2020), which could remove its constraint on the DW1. Such effect of small-scale gravity wave flux in modifying the tidal structure on Mars needs more studies in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Since the gravity wave energy and momentum flux are proportional to the square of the wave amplitude, the increase in observed amplitude is, in fact, even higher in terms of these dynamically important quantities. An overall effect of storms on the lower atmosphere is the convective (Figure 1c of Kuroda et al, 2020) and baroclinic (Figure 2 of Kuroda et al, 2007) major mechanisms of GW generation in the lower atmosphere. Observations by Mars Climate Sounder provided evidence of a reduction of GW activity below 30 km by several times during the 2018 GDS (Heavens et al, 2020).…”
Section: Mechanism Of Dust-induced Gravity Wave Enhancementmentioning
confidence: 99%
“…Finally, we have to note that the measured wind velocities maintain its high values on 31 August as seen in Figure 3; while, the dust storm was significantly weaker by the end of August (Fedorova et al, 2020;Luginin et al, 2020). According to the model prediction by Kuroda et al (2020), the impact of dust storms on the zonal winds is essentially the same regardless of the extent of the storm. The discrepancy between our result and dust storm evolution might suggest a bias of the wind determination in our result.…”
Section: Discussionmentioning
confidence: 74%
“…The observed enhancement of the retrograde (easterly) equatorial wind in the mesosphere during dust storms has been captured by the MGCMs (Kuroda et al, 2020;Medvedev et al, 2013;Ruan et al, 2019). Medvedev et al (2013), with a horizontal resolution of ∼5.6° in both longitude and latitude and a gravity wave drag parameterization empirical for terrestrial thermosphere (Yiǧ;, presented simulations based on the zonally averaged dust distributions observed by the Thermal Emission Spectrometer instrument (TES) onboard the Mars Global Surveyor (MGS) during the 2001 PEDE (MY25), which started at almost the same season as the one in 2018.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation